Influence of investment environment and development of infrastructure investment technology on state management of effective infrastructure development investment - Thu, Nguyen Van; Hung, Pham Thanh; Phuong, Ha Thi Thu; Mai, Nguyen Chi; Phong, Bui Xuan (Edelweiss Applied Science and Technology, 2025)
The awareness of party committees, party organizations, authorities, enterprises, and society about the role and special importance of infrastructure for socio-economic development, industrialization, and modernization of the country has seen many positive changes. The legal system has been improved, approaching international practices, especially policies on planning, development investment, public investment, and public-private partnerships. Many programs, projects, and works have been put into operation and effectively promoted, especially in transport infrastructure, energy, irrigation, urban areas, and information and communication. However, some of these results have not met the requirements, have not created a breakthrough in mobilizing resources, have not formed a synchronous and modern infrastructure system, and have not ensured rapid and sustainable development. Through qualitative and quantitative research methods, the objective of this article is to study the influence of the investment environment and the development of infrastructure investment technology on the effective state management of infrastructure development investment in Quang Ninh province. The results show that the development of infrastructure investment technology positively affects the effective state management of infrastructure development investment in Quang Ninh province. From there, some recommendations are proposed to improve the effectiveness of state management of infrastructure development investment in Quang Ninh province.